Energy Analysis Power of the Nuclear Track Detector PM-355 for Alpha Particles - S. H. S. Al-Nia’emi; M. M. S. Al-Jobouri (Jordan Journal of Physics, 2025)
Extended Abstract: When a heavy charged particle passes through matter, it loses energy principally by scattering electrons within the matter it passes through it and will cause extensive ionization of the material through ionizing the atoms or molecules close to its path. Thus, the charged particle gradually loses its energy and is subjected to a gradual slowing down that could make it stop at the end of the path within the medium. The average energy loss of the particle per unit path length (dE/dx) is called the linear stopping power (S), which may be measured in units of MeV/cm or similar. The stopping power and hence, the density of ionization, usually increases toward the end of the range of the particle and reaches a maximum, the Bragg edge, shortly before the energy drops to zero. The curve that describes this is called the Bragg curve. The ionization processes can be treated statistically to derive the equation of stopping power, the best known being the Bethe formula. . . . Keywords: Nuclear tracks, PM-355, Energy analysis or resolution, Isotopes, Isotope identification.